2010
DOI: 10.1007/s10997-010-9128-3
|View full text |Cite
|
Sign up to set email alerts
|

The changing role of the supervisory board chairman: the case of the Netherlands (1997–2007)

Abstract: Over the last ten years, the corporate governance context in most Western countries has changed as a result of irregularities, increased regulation, heightened societal expectations and shareholder activism. This paper examines the impact of the changing context on the role of chairmen of supervisory boards in the Netherlands. Based on a combination of thirty semi-structured interviews with board members of leading Dutch corporations and secondary data on the position of supervisory board chairmen at the top-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Model 3a, Model 3b and 3c model also showed an increase of respectively 3.2% and 3.9% of the company's performance. These findings are consistent with evidence from Bezemer et al (2007Bezemer et al ( , 2012 in their study in the Netherlands with the finding that the two boards gave wider opportunities to the majority shareholders to play a role in overseeing the operations of the firm through a separate board up can have an impact on firm performance. Another reason that may be attributed to the above findings is the average equity holdings by individuals and families who are at a high level, which is 49.53% and is seen more concentrated compared to the situation in countries that have a system of a board (Kamal, 2010).…”
Section: The Effects Of Family Ownership On Firm Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…Model 3a, Model 3b and 3c model also showed an increase of respectively 3.2% and 3.9% of the company's performance. These findings are consistent with evidence from Bezemer et al (2007Bezemer et al ( , 2012 in their study in the Netherlands with the finding that the two boards gave wider opportunities to the majority shareholders to play a role in overseeing the operations of the firm through a separate board up can have an impact on firm performance. Another reason that may be attributed to the above findings is the average equity holdings by individuals and families who are at a high level, which is 49.53% and is seen more concentrated compared to the situation in countries that have a system of a board (Kamal, 2010).…”
Section: The Effects Of Family Ownership On Firm Performancesupporting
confidence: 89%
“…In the short term, this behavior will maintain the performance, while the performance of the firm can be done gradually in the long run. Consistent with this point, Bezemer et al (2007Bezemer et al ( , 2012 found in his study that the BOC members involved in controlling BOD managers can improve compliance and reduce the risk of failure but reduced in other firms focusing on innovation and research and development firms (Hendry & Kiel, 2004;Sundaramurthy & Lewis, 2003). On the other hand, family involvement in the two boards reduces conflicts of interest between the BOC and BOD and provides a positive influence on firm performance.…”
Section: The Effect Of Family Involvement In Both Boards (Boc and Bodmentioning
confidence: 84%
“…Boards of directors are at a crucial intersection between the environment and the firm's strategy, and they have a fiduciary duty to contribute their knowledge resources in pursuit of organizational wellbeing (Bezemer et al, 2012;Boyd, 1990;Pugliese et al, 2009;Tuggle et al, 2010;Yawson, 2006). Boards are increasingly expected to be participants in strategy-making (e.g., Hendry, Kiel, and Nicholson, 2010;Kor and Sundaramurthy, 2009;McNulty and Pettigrew, 1999;Ruigrok, Peck, and Keller, 2006;Stiles, 2001) and are a source of knowledge accumulated through professional formative experiences such as expertise in particular organizational functions (Menz, 2012;Tuggle et al, 2010).…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…The classical management approach concerns to threaten workers as machine (Bell and Martin, 2012). In the context of SMEs, greater involvement of owner managers is important for the role of managers, while the control system, compliance and shareholder value may encourage firms to be more risk-aversion, focus on short-term efficiency and less focus on innovation (Bazemer et al, 2012).…”
Section: Contingency Theorymentioning
confidence: 99%